ANALISIS PENGARUH PAJANAN KEBISINGAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI PT. KIRANA MUSI PERSADA - Nur Afni Maftukhah (Masker Medika, 2024)
Labor is an important factor for a company, one of the parameters that can be used to assess the quality of labor is work productivity. Work productivity aims to see the extent to which the workforce can provide optimal contributions in efforts to achieve company goals. In order for a company's productivity to increase, the company must try various ways, one of which is by creating comfortable, safe and peaceful working conditions for employees who work in the company. One of the health factors in the industrial work environment is noise. Objective : To determine the relationship between the influence of noise exposure on employee work productivity at PT. Kirana Musi Persada. Method : Quantitative research uses the Observational Analytical method with a Cross Sectional approach. Noise data samples were taken at 8 points using a sound level meter, while 119 employee productivity data samples were taken using a questionnaire. Results : The results of research using Chi-square obtained a p value = 0.013 or p-value < 0.05 which shows there is a relationship between noise intensity and employee work productivity and a p value = 0.431 or p-value > 0.05 which shows there is no relationship between length of service and productivity employee work to get value. Suggesstion : Reducing sources of sound from production machines and heavy equipment by carrying out repair maintenance on machines that experience malfunctions, equipping machines with sound dampening devices so that they do not exceed the threshold value, Providing outreach, seminars and training to employees about the dangers of noise and its control. Discussion : The threshold value (NAB) for physical factors and chemical factors in the workplace environment, especially noise exposure in the workplace, is 85 dBA for exposure 8 hours a day or 40 hours a week.